Software quality assurance through COSMIC FFP. - Zayaraz, G.
Success in software development depends on the satisfaction of the quality requirements stated by the stakeholders. Software architecture ensures development of quality software. Quality measurement at the software architecture level leads to risk mitigation, cost reduction and quality assurance. Existing software architectural measurement techniques are qualitative in nature. However, quantification of quality measures facilitates the process of effective quality assurance. In this paper, we propose a new quantitative measurement technique based on COSMIC Full Function Points (CFFP) and ISO 9126 quality standards. Though CFFP methodology was basically designed to measure the functional size of software at the requirements level, attempt has been made to apply COSMIC FFP principles at the architectural level to measure quality attributes based on ISO 9126 quality standards.
Keywords: Software; Software engineering; Management; Software quality assurance (SQA).; General; Standards; Software architectures; Design; Management; Performance; Standardization; Cosmic FPP; Cohesion; Complexity; Coupling; Quality attributes; Software architecture